Cypherpunks : freedom and the future of the internet - Assange, Julian (OR Books, 2012)
Cypherpunks are activists who advocate the widespread use of strong cryptography (writing in code) as a route to progressive change. Julian Assange, the editor-in-chief of and visionary behind WikiLeaks, has been a leading voice in the cypherpunk movement since its inception in the 1980s. Now, in a wave-making new book, Assange brings together a small group of cutting-edge thinkers and activists from the front line of the battle for cyber-space to discuss whether electronic communications will emancipate or enslave us. Do Facebook and Google constitute "the greatest surveillance machine that ever existed"? Far from being victims of that surveillance, are most of us willing collaborators? Are there legitimate forms of surveillance, for instance in relation to the "Four Horsemen of the Infopocalypse" (money laundering, drugs, terrorism and pornography)? And do we have the ability, through conscious action and technological savvy, to resist this tide and secure a world where freedom is something which the Internet helps bring about?